The Relationship of The Physical Quality of The House and Personal Hygiene with Dermatitis in Juai District - Febrianty, Ersha; Santoso, Imam; Erminawati, Erminawati; Rahmawati, Rahmawati (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2023)
Dermatitis is a skin disorder that appears inflamed and irritated. There are two factors that influence the occurrence of dermatitis: exogenous factors (chemicals, microorganisms, temperature, and humidity) and endogenous factors (personal hygiene, skin thickness, age, gender, and disease history). In 2020, the Balangan District Health Office recorded data showing dermatitis as the 6th most common disease among the community from various sub-districts in Balangan Regency, with Juai being the sub-district with the highest number of dermatitis cases. In Juai, the Balangan District Health Office recorded 519 cases of dermatitis in 2020. This study was aimed at determining the relationship between the physical environment of the house, personal hygiene, and dermatitis in the community. We conducted this research as an analytical survey, utilizing a case-control research design. The sample consisted of 43 cases and 43 controls. The instruments used were a thermohygrometer, a lux meter, and a questionnaire. Some cases involved the use of data analysis. Statistical test results In Juai District, Balangan Regency, Somers'd revealed a significant correlation between the physical environment of the house (temperature p = 0.001, humidity p = 0.004, and lighting p = 0.002), personal hygiene (p = 0.018), and dermatitis. Patients with dermatitis should avoid allergen-triggering substances found in daily products and improve habits that can trigger dermatitis.